Impact of Timanian thrusts on the Phanerozoic tectonic history of Svalbard - Koehl, Jean-Baptiste P. (2019)
Presentation at "Friday seminar" at UiT The Arctic University of Norway, 13.09.2019. Despite more than a century of investigation, the relationship between basement rocks throughout the Svalbard Archipelago is still a mystery. Though these rocks display similar geochronological ages, they show significantly different metamorphic grades and structures. Thus far, Svalbard was believed to be composed of three terranes of rocks formed hundreds–thousands of kilometers apart and accreted in the mid-Paleozoic. New evidence from seismic, gravimetric, aeromagnetic, seismological, bathymetric, and field data show that these terranes might have already been accreted in the late Neoproterozoic. Notably, the data show that at least three–four, crustal-scale, WNW–ESE-striking thrust systems crosscut Spitsbergen and merge with Timanian thrusts in the northern Barents Sea and northwestern Russia. These thrusts were reactivated as sinistral-reverse oblique-slip faults and partly folded during the Caledonian and Eurekan orogenies, and reactivated as sinistral-normal faults during Devonian–Mississippian extensional collapse, thus offsetting N–S-trending Caledonian grain and post-Caledonian basins. The presence of these faults explains the juxtaposition of basement rocks of seemingly different origin throughout the Svalbard Archipelago, the distribution of Mississippian rocks and Early Cretaceous intrusions along a WNW–ESE-trending axis in central Spitsbergen, the west vergence of Cenozoic folds in Devonian rocks in central–northern Spitsbergen (previously ascribed to Late Devonian Ellesmerian contraction), the arch shape of the Cenozoic West Spitsbergen Fold-and-Thrust Belt in Brøggerhalvøya, and the strike and location of transform faults west of Spitsbergen. Further implications of this work might be that the tectonic plates constituting present-day Norwegian Arctic regions (Laurentia and Baltica) have retained their current geometry and alignment for the past 600 Ma, that the Timanian Orogeny and associated WNW–ESE-striking ...